Effects of Antigen-Antibody Complexes on the Primary Immune Response in Rhesus Monkeys - Houston, W. E. (1974)
A model for the enhancement of the primary humoral immune response of rhesus monkeys to marginal or weakly antigenic vaccines is presented. Our procedure used the complexing of formalin-inactivated Venezuelan equine encephalomyelitis (VEE) virus vaccine with specific, homologous, immune gamma globulin (IgG) at equivalence. Equivalence was determined by combining the concentrated, isotopically labeled ((3)H) virus with various concentrations of specific Sephadex-fractionated IgG. Enhancement of VEE virus antibody response in monkeys was obtained from preparations containing a marginal concentration of antigen that was complexed at equivalence with homologous IgG as compared with antigen alone. Protection in Swiss mice closely paralleled the antibody response pattern observed in monkeys, since complexes at equivalence provided 30 to 50% greater protection against challenge than antigen alone.